Dr. Vekoslav Grmič skozi oči svetovnonazorske ateistke - Černe, Igor (Časopis za zgodovino in narodopisje, 2023)
In a way, this article serves as a tribute to Cvetka Hedžet Tóth, who made a significant impact in the Slovenian community with her humanistic approach. The discussion is based on two aspects: the first being personal memories of the author, who was wrote about Bishop Dr Vekoslav Grmič, which are compiled in the book “Vekoslav Grmič – Bishop Witness”. Grmič’s thoughts resonated with her, and she used them as a foundation to develop her own ideas. Despite coming from different backgrounds, they connected on a personal and academic level. Together, they addressed societal issues and drew inspiration for their own worldviews.
Keywords: filozofija; globalizem; Grmič, Vekoslav; Hedžet Tóth, Cvetka; humanizem; spomini; teizem; toleranca